Chronic low-dose REV-ERBs agonist SR9009 mitigates constant light-induced weight gain and insulin resistance via adipogenesis modulation - Ming-Yu Yang; Hugo Y.-H. Lin; Yi-Ywan M. Chen; Ming-Luen Hu; I-Ya Chen; Chao-Hui Yang (Biomedical Journal)
Background: Obesity and circadian rhythm disruption are significant global health concerns, contributing to an increased risk of metabolic disorders. Both adipose tissue and circadian rhythms play critical roles in maintaining energy homeostasis, and their dysfunction is closely linked to obesity. This study aimed to assess the effects of chronic low-dose SR9009, a REV-ERB ligand, on circadian disruption induced by constant light exposure in mice. Material and methods: Mice were exposed to constant light for eight weeks (LL mice), resulting in increased body weight, insulin resistance, white fat mass, and altered circadian clock gene expression. Low-dose SR9009 (10 mg/kg daily) was administered chronically to assess its impact on these metabolic disruptions. Results: LL mice treated with SR9009 for eight weeks showed reduced weight gain, insulin resistance, and white fat mass but no significant impact on overall energy homeostasis. SR9009 suppressed Bmal1 expression and restored Rev-erbα and Rev-erbβ expression in white and brown adipose tissue (WAT and BAT). In vitro studies using 3T3-L1 cells indicated that SR9009 inhibited adipogenesis, leading to further investigation in vivo. SR9009 restored ChREBP1a and Srebp-1c expression in BAT but did not affect inflammatory cytokine or adipokine gene expression, nor did it restore Fasn, Pparγ, and Prom1 expression in both WAT and BAT. Conclusions: These findings suggest that SR9009 may be a potential therapeutic approach for preventing weight gain and insulin resistance caused by circadian disruptions, likely through adipogenesis inhibition, though its effects on other metabolic pathways remain limited at low doses.